Human cardiomyocytes for drug discovery - Diogo Gonçalves Biagi; Jéssica Gonçalves; Estela Cruvinel; Renata Damiani; Flavia Valgode; Fabiana Medeiros; Camila G Moreira; Evelyn Santos; Rodrigo Marcon; Calixto João; Gabriela Venturini; Alexandre Pereira; et al. (Fundação Oswaldo Cruz (FIOCRUZ), 2018)
Introduction: Cardiac drug discovery are based in old methods that use animals, animal cells or modified cells that do not faithfully represent human cardiac phenotypes. Objective: Here, we aimed to show that cardiomyocytes derived from human iPS cells represent a new tool for cardiac drug discovery and could contribute do reduce animal use in research. Method: Generation of human iPS cells derived  cardiomyocytes and its use for cardiotoxicity evaluation and infection with T. cruzi for drug discovery. Results: Definition of robust protocol for human iPS cells reprogramming, maintenance and cardiac differentiation. Derivation of high purity cardiomyocytes from hiPSCs that presented toxicity to different doses of doxorubicin and were amenable to infection of T. cruzi. Conclusions: Human cardiomyocytes derived from human iPS cells can be a great tool for drug discovery and can replace several assays done in animals helping to reduce animal use in research.